Pengaruh Tenaga Kerja, Modal dan Bahan Baku Terhadap Produksi Industri Kerajinan Patung Kayu di Kecamatan Tegallalang - Agustina, I Made; Kartika, I Nengah (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2017)
The small and medium industrial sector in Tegallalang Distric highly develoved one of them is in the industrial sector wood statue handicraft be able to absorbing manpower and open business field. This research is associative and located in Tegallalang Distric Gianyar Regency with the number of respondents is 38 business unit craftsman wood statue. The purpose of this research to analyze the influence variable of labor, capital, and raw materials to the production of industrial wood statue handicraft in Tegallalang Distric Gianyar Regency with technique Cobb-Douglas linear regression analysis. The results of the analysis showed that simultaneously variable labor, capital, and raw materials have had a positive impact and significant impact on the production of industrial wood statue handicraft in Tegallalang Distric Gianyar Regency. Test results in partial showed that variable labor in partial do not affect on the production of industrial wood statue handicraft in Tegallalang Distric Gianyar Regency. Variable capital and raw materials in partial have had a positive impact and significant impact on the production of industrial wood statue handicraft in Tegallalang Distric Gianyar Regency. The dominant influences variables to the production of industrial wood statue handicraft  was variable raw materials.
Keywords: Tenaga Kerja; Modal; Bahan Baku; Produksi